Real-time nanoleakage and the flow characteristics of calcium silicate root canal filling materials. (December 2020) - Park, Su-Min; Yoo, Yeon-Jee; Lee, In-Bog; Lee, WooCheol
Abstract: This study aimed to investigate the real-time nanoleakage and flow characteristics of calcium silicate-based (Ca–Si) root canal filling materials. Extracted human teeth ( n  = 30) were decoronated and standardized in their inner and outer dimensions. After root canal enlargement, the roots were filled with gutta-percha (GP) and AH26 sealer, GP and EndoSeal MTA sealer, or Biodentine. The roots were connected to a Nanoflow device (IB Systems) under hydrostatic pressure (40 cm∙H2 O) and fluid flow was traced through the filled roots. Data were detected at the nanoscale twice per second and automatically recorded in units of nL/s. Leakage was quantified as the mean slope until the curve plateaued over time, and all static flow intervals lasting longer than 1 s were analyzed to identify any increase in flow and duration. Data were statistically analyzed using the Kruskal-Wallis test. The calculated leakage values were 0.0670 ± 0.0516 nL/s for GP/AH26, 0.1397 ± 0.1579 nL/s for GP/EndoSeal MTA, and 0.0358 ± 0.0538 nL/s for Biodentine, with no statistically significant differences among the root filling materials ( P  > 0.05). An analysis of real-time flow data for 1000 s to identify spot trends and the overall tendency of flow until a plateau was reached revealed a stepwise increase in the roots filled with Ca–Si material, whereas the GP/AH26-filled roots showed a linear increase. Real-time measurements under hydrostatic pressure with the Nanoflow device enabled precise fluid flow tracing through the root canal filling material. In terms of nanoleakage, the tested root canal filling materials showed no significant differences, while the real-time flow patterns of roots filled with Ca–Si material showed different characteristics from those of GP/AH26-filled roots. Highlights: Most studies focus on open pores between gutta-percha, endodontic sealer, and root dentin with micro-CT that are potential niches for bacterial growth and migration pathways. But static evaluation cannot obviate inappropriately filled roots that bias results. This study investigated the nanoleakage of Ca-Si root canal filling materials and characterized their fluid flow patterns in real-time, to reconsider leakage or porosity researches and provide relevant scientific evidence in endodontic aspect.